The Role of Islamic Spirituality in Parent-Child Relationships: Perspectives from Muslim Counselors - Leli Nurlaili (Sekolah Tinggi Agama Islam Kuningan, 2025)
The dynamics of parent-child relationships are deeply influenced by cultural and spiritual values, particularly in Muslim families where Islamic teachings significantly shape interpersonal interactions. This study explores the role of Islamic spirituality in enhancing parent-child relationships, drawing insights from the lived experiences of Muslim counselors. The primary objective is to examine how Islamic spiritual principles—such as tawakkul (trust in God), shukr (gratitude), and sabr (patience)—are integrated into parenting approaches and how these influence emotional bonding and communication within the family. Employing a qualitative phenomenological method, the study involved in-depth semi-structured interviews with 15 Muslim counselors in Indonesia and Malaysia who have professional experience in family and child counseling. Thematic analysis revealed that Islamic spirituality fosters mutual respect, emotional warmth, and moral development in parent-child interactions. Counselors emphasized that integrating religious values into parenting not only supports children's behavioral and emotional regulation but also strengthens parental resilience and empathy. These findings align with and extend prior research on spiritual attachment theory and religious coping strategies in family dynamics. The study contributes to a nuanced understanding of culturally embedded parenting frameworks and offers practical implications for counseling practices by promoting the inclusion of faith-based approaches. Future research is recommended to explore longitudinal impacts of spiritual parenting in diverse Muslim contexts and to develop intervention models integrating Islamic spiritual values in family counseling.